2020
DOI: 10.1017/s1049023x20001314
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Survival in Adult Trauma Patients Transported to US Trauma Centers by Police

Abstract: Introduction: Police units often reach the trauma scene before Emergency Medical Services (EMS). Initiatives aiming at delivering early basic trauma care by non-medical providers including police personnel are on the rise. This study describes characteristics of trauma patients transported by police to US hospitals and identifies factors associated with survival in this patient population. Methods: Using the 2015 National Trauma Data Bank (NTDB), an observational study was conducted of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Consistent with a previous report from Malawi, transportation to the hospital by the police was the most predictive factor of an early death, increasing the risk by nearly 50% [17]. The role of police in transporting injured patients from the scene has been controversial in the United States, with conflicting evidence about the safety and timeliness of transfer [18][19][20]. Data from neighboring countries in sub-Saharan Africa have been mixed, with some reports showing no adverse outcomes related to police transport [21,22].…”
Section: Discussionsupporting
confidence: 59%
“…Consistent with a previous report from Malawi, transportation to the hospital by the police was the most predictive factor of an early death, increasing the risk by nearly 50% [17]. The role of police in transporting injured patients from the scene has been controversial in the United States, with conflicting evidence about the safety and timeliness of transfer [18][19][20]. Data from neighboring countries in sub-Saharan Africa have been mixed, with some reports showing no adverse outcomes related to police transport [21,22].…”
Section: Discussionsupporting
confidence: 59%
“…9,14 A previous study assessing factors associated with survival of trauma patients transported by police showed that ISS along with other factors such as a GCS ≤ 8 and a SBP below 90mmHg were associated with lower survival to hospital discharge. 13 Beyond the potential medical benefits, incorporating PT of trauma patients to hospitals can be associated with positive outcomes. In previous studies out of the US, patients transported by police belonged to racial minority groups that have little a "Other" is the combination of the following nature of injuries: Amputations, Burns, Crush, Dislocation, Nerves, Sprains & Strains, System Wide & Late Effects, Unspecified.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study using the US National Trauma Data Bank (NTDB; American College of Surgeons; Chicago, Illinois USA) showed a high survival rate (93.5%) for trauma patients who were transported by police when compared to previous survival rates of trauma patients transported by EMS in other studies. 13 Current evidence regarding penetrating trauma patient outcomes in police transport (PT) is scarce. Previous studies showed that PT of penetrating injuries is not associated with a mortality difference when compared to EMS transport of similar injuries, 10 and some showed improved survival with PT in sub-group analysis including only severely injured patients.…”
Section: Introductionmentioning
confidence: 99%
“…8,30 Significant differences in terms of survival are reported when studies take into consideration variation in prehospital times. 8,9,31 Factors associated with survival in patients transported by police were previously examined, 10 and blunt trauma mainly from motor vehicle traffic was identified to be a significant positive predictor of survival.…”
Section: Discussionmentioning
confidence: 99%
“…8 Involvement of police in trauma transport is based on the principle of the golden hour, which pertains to efficient prehospital care and rapid arrival to the hospital. 9,10 As law enforcement, officers usually arrive at the trauma incident location prior to ground ambulance; they are increasingly involved in prehospital care and rapid transport to the ED. [11][12][13][14] In Philadelphia (Pennsylvania USA), a well-defined prehospital protocol requires law enforcement officers to transport penetrating trauma patients to the nearest trauma center since 1996.…”
Section: Introductionmentioning
confidence: 99%